To become a teacher: an art that unfolds along the way (Revista Contexto & Educação, 2025)
This study centers on the discussion of becoming a teacher. Therefore, the main objective is to present the perceptions of the teachers participating in the Emotional Education Research Group (GRUPEE) at the Universidade Federal da Fronteira Sul – UFFS, regarding the academic and professional paths experienced that enabled them to become teachers. The qualitative research approach utilized the Padlet platform, where participants recorded their responses to the question: What academic and professional paths have enabled you to become a teacher? The literature review drew from authors such as Josso (2004), Zeichener (1993), and Day (2001). The analysis of the narratives, which is descriptive-interpretative in nature, shows that the process of becoming a teacher is influenced by a variety of formative experiences and professional development. The participants' narratives emphasize the importance of initial training, the need for continuous education, and the sharing of experiences with fellow teachers as learning and professional growth. The process of becoming a teacher is dynamic and continuous, involving the integration of theoretical and practical knowledge, as well as personal and professional experiences, for the holistic development of the profession
Keywords: Teacher education; Academic and professional paths; Professional development